Tahap kekhuatiran komunikasi dalam kalangan pelajar Universiti Utara Malaysia - Dalib, Syarizan (Universiti Utara Malaysia, 2008)
Communication incompetence among graduates is seen as one of the factors that cause graduates unemployment.However, in the midst of this issue, there is a lack of attention being given to understand graduates problems in obtaining communication skills.Hence, this research aims at focusing on understanding a barrier to communication skills among graduates which is called Communication Apprehension (CA). This research is conducted to identify the level of communication apprehension among Universiti Utara Malaysia students.Specifically, this research seeks to identify level of the students’ overall CA and their level of CA in four communication contexts: public speaking, classroom interactions, small group communication and interpersonal communication.The research utilizes quantitative method. Data was collected through questionnaires in that Personal Report on Communication Apprehension (PRCA-24) was distributed to undergraduate students of Communication program.356 students were involved in this research. The data was analyzed using descriptive and inferential analysis.Results reveal that most of the students (72%) are moderate in their level of CA, 21% are low in their score of CA level and only 7% suffer from high level of CA.A specific analysis on CA in the four communication contexts shows that students’ level of CA are higher in public speaking and classroom interactions than interpersonal communication and small group communication context.This research also found that there is a significant difference between male and female students in their level of CA. Female students are higher in the level of CA than male students.Result also found that there is a significant difference of CA level between races in which Chinese students are more apprehensive than other races.Several implications and suggestions are discussed in this report.